Implementasi Evaluasi Pembelajaran sebagai Instrumen Peningkatan Kualitas Belajar dalam Kurikulum Merdeka - Hendriyansyah Hendriyansyah; Maria Ulfa Yundiafi; Devi Marilawati; Mustaqim Hasan (Concept: Journal of Social Humanities and Education, 2026)
The Merdeka Curriculum introduces a paradigm shift in Indonesia's educational assessment system, moving from an outcome-oriented approach toward one that positions evaluation as an integral part of the learning process itself. This article examines how learning evaluation is implemented as an instrument to improve the quality of student learning within the Merdeka Curriculum framework. This study employs a library research method, analyzing relevant policy documents, regulations, and academic literature. The findings indicate that the Merdeka Curriculum shifts the focus of evaluation from mere measurement (assessment of learning) toward assessment as learning and assessment for learning, realized through three main forms of assessment: diagnostic, formative, and summative. Proper implementation of these three forms enables teachers to map students' individual learning needs, provide continuous feedback, and design differentiated instruction that is more relevant to learners' characteristics. However, field implementation still faces several challenges, including uneven teacher understanding, time constraints, and limited technical training in designing authentic assessment instruments. This article recommends strengthening teacher competence, providing practical technical guidance, and offering continuous mentoring as strategic steps to ensure that learning evaluation truly functions as an instrument for improving learning quality, rather than merely an administrative formality.